2017
DOI: 10.1155/2017/8430943
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Integrated Aerodynamic Protuberant Foil Journal and Thrust Bearing in Turboexpander

Abstract: Foil bearing provides compliant support and moderate Coulomb friction for rotor-bearing system, which is conducive to stability and reliability of high speed rotating machinery. In this paper, both hydrodynamic lubricated foil journal and foil thrust bearings are applied in a 150 m 3 ⋅h −1 turboexpander for air separation. In the bearings, protuberant foil is chosen as the supporting subfoil due to its merits of easy fabrication and assembly. Static loading and deflection of the bearings are tested, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The performance of FTB in terms of coefficient of friction, load capacity, and temperatures was evaluated for grooved foils by Hyuga and others [2] for lower speeds. Similar performance tests were conducted on hydrodynamic gas foil journal bearing (GFJB) and foil thrust bearing (FTB) on a turbo-expander by T Lai et al [3] for rotating speeds up to 52,000 rpm. Effect of foil stiffness and RESEARCH nominal clearance on static performance of GFTB with top foil, bump foil, and supporting foil were tested for a centrifugal air compressors by Ting Shi and others [4].…”
Section: Introductionmentioning
confidence: 88%
“…The performance of FTB in terms of coefficient of friction, load capacity, and temperatures was evaluated for grooved foils by Hyuga and others [2] for lower speeds. Similar performance tests were conducted on hydrodynamic gas foil journal bearing (GFJB) and foil thrust bearing (FTB) on a turbo-expander by T Lai et al [3] for rotating speeds up to 52,000 rpm. Effect of foil stiffness and RESEARCH nominal clearance on static performance of GFTB with top foil, bump foil, and supporting foil were tested for a centrifugal air compressors by Ting Shi and others [4].…”
Section: Introductionmentioning
confidence: 88%
“…In 2012, in order to analyze the feasibility of the application of protuberant foil journal bearings in a turbo-expander, another experimental study was carried out. The results showed that the maximum speed of the turbo-expander reached 99,044 rpm, and the low-frequency whirl motion was small during the entire speed-up and speed-down process [45][46][47]. In the total protuberant foil bearing test (both journal and thrust bearings are protuberant type), the gas foil bearing ran smoothly and had high repeatability during the operation of the turbo-expander [15].…”
Section: Application In Low Temperature High-speed Turbo-expandermentioning
confidence: 99%
“…In addition to bump foils can be used as bearing support components; protuberant foils can also be used as bearing elastic support components to form protuberant foil bearings (Hou et al, 2011;Lai et al, 2017;Pan et al, 2018;Zheng et al, 2016aZheng et al, , 2016b. For this type of bearing, researchers have also tried to use double foil to improve the performance of bearings.…”
Section: Introductionmentioning
confidence: 99%